Exploring the user interface of negotiation support systems from the user acceptance perspective. - Lee, Kun Chang; Kang, Inwon; Kim, Jin Sung (Computers in Human Behavior, 2007)
Despite the fact that Web-based negotiation support systems (NSS) have gained momentum in B2B electronic commerce, there have been few studies investigating the way the NSS interface might be utilized to promote user acceptance. This paper presents the results of an empirical study investigating NSS, from a user acceptance perspective and utilizing a technology acceptance model. We have explored the influence of three constructs embedded in NSS: playfulness, causality and subjective norm. The role of causality, in particular, has never been tested within the context of user interface and user acceptance of the system, so we developed a prototype NSS called CAKES-NEGO. Empirical results garnered from 174 valid questionnaires proved the validity of our proposed research model: the NSS user interface, embedded with the three constructs, causes users to consider the system more favorably. Copyright (c) 2006 Elsevier Ltd